Do visível ao invisível : as ruas de pedras da Cidade de Goiás e a invenção do patrimônio cultural (1950-1978) - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This study analyzes the stone-paved streets of the historic center of the city of Goiás, recognized as cultural heritage, with the aim of understanding their formation and their relationship with the heritage processes carried out locally by DPHAN/IPHAN in the 1950s and in 1978. The main objective of the research was to identify the starting point of the transformations in the cultural landscape, specifically in the paving of the streets, and to examine how such interventions were used to compose the “invention” of heritage, encompassing memory, identity, and power. The methodology adopted was based on exploratory research, including the analysis of photographs, handwritten documents, literary works, and bibliographic references related to the theme. The results of the investigation revealed that the physical interventions carried out in the streets not only shaped the urban structure but were also instrumentalized in the construction of an idealized narrative about the city’s past. Although associated with an ideal of preservation, heritage processes involve complex social choices and negotiations, as they represent historical “selections” that define which cultural assets will be deemed worthy of preservation and which will be forgotten. In the physical representations linked to heritage symbols, reconfigurations of meaning or the appropriation of elements from different periods may occur. In this context, heritage assets may be “invented” to provide cohesion to a homogenizing discourse, oriented by specific interests and the exercise of power through heritage. As a complementary product to the technical report, a video was produced, presenting various images and footage of the historic center of Goiás, interspersing records from different periods, which attest to the modifications in the cultural landscape from the early twentieth century to the present day (2025).
From the visible to the invisible : the cobble streets of GOIás City and the invention of cultural heritage (1950-1978)
Keywords: Patrimônio cultural; Invenção; Cidade de Goiás; Centro histórico; Ruas de Pedras; Calçamento; Cultural heritage; Invention; City of Goiás; Historic center; Stone-paved streets; Pavement; CIENCIAS HUMANAS::HISTORIA; HISTORIA::HISTORIA DO BRASIL; HISTORIA DO BRASIL::HISTORIA REGIONAL DO BRASIL